Rate of physical appearance changes on yellowness in salak during preservation in room storage - Pangestika, Widia; Al-Baarri, Ahmad Ni’matullah; Legowo, Anang Mohamad; Hadipernata, Mulyana; Broto, Wisnu; Izzati, Laili (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Discoloration was one indicator of food damage including in fruits, since the change may be used as a quality measurement. Salak became one of the commodities that often experience the browning reaction that may change the color. Since the yellow was close to the consumer preference along the preservation in salak, this color should be notified and may be represented as polyphenol change. Objectives: The focus of this study was to determine the pattern of inhibition of browning reactions in salak using HIO.Methods: This research determined the color level of yellow using digital color meter of salak that was stored in room temperature in aseptic treatment for 12 days. Result: Discoloration appeared in salak and it was clearly determined the change since a week of storage. The rate of discoloration was able to be detected highly after one week of storage. Conclusion: The discoloration of yellow color and the rate of salak could be detected specifically based on the day of storage. This research may open the information for the consumer to predict the storage time of salak based on the appearance of yellow color.